ANALISIS PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM INDEKS LQ45 PERIODE 2016 – 2018 - Fika Elfiana; Untung Sriwidodo; Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research aims to analyze the significance of the influence of Current Ratio, Return On Equity and Earning Per Share on Stock Prices LQ45 Index, both partially and simultaneously. The data used in this research are quantitative data in the form of the company's annual financial statements published by the Indonesia Stock Exchange for the period 2016 – 2018. This research uses a purposive sampling technique with a sample of 30 companies from 59 companies listed on the LQ45 Index for the period 2016 – 2018. The analysis technique uses multiple linear regression. Hypothesis test results show that Earning per Share have a significant effect on Stock Prices, while Current Ratio and Return On Equity has no significant effect on Stock Prices. Investors should review financial statements issued by the company and use financial ratios as a reference in investing.